Pengaruh Financial Distress, Growth Options, Institutional,Ownership Terhadap Aktivitas Hedging: - Dian Yustika; Charoline Cheisviyanny; Nayang Helmayunita (Universitas Negeri Padang, 2019)
This,research aims to examine,at the,influence of financial distress, growth options, and institutional ownership against hedging activity on manufacturing company in Indonesia stock exchange period 2014-2016. To achieve that goal, this ,research using,quantitative.research methods to examine the population or a specific sample in,order to test the,hypothesis that,have been set. The.technique of data collection is done by libraries and,documentation techniques.,This research using the method,of logistic regression because this method is the most representative to,examine,the variables examined. The results of this research,indicate: (1) Financial distress had no effect significant hedging,activity,against (2) Growth of significant positive effect Options against hedging,activity (3) Institutional ownership of significant effect against hedging activities